2015
DOI: 10.1002/2015gl066154
|View full text |Cite
|
Sign up to set email alerts
|

Consistent decrease in North Atlantic Tropical Cyclone frequency following major volcanic eruptions in the last three centuries

Abstract: Injection of sulphate aerosols into the stratosphere following major volcanic eruptions alters global climate through the absorption and scattering of solar radiation. One proposed consequence is a decrease in North Atlantic Tropical Cyclone (TC) activity, as was observed following the El Chichón (1982) and Mount Pinatubo (1991) eruptions. We test this relationship using documentary and proxy reconstructions of major volcanic eruptions and TC frequency in the North Atlantic basin over the last three centuries.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 46 publications
3
21
0
Order By: Relevance
“…3). The large influx of sulphate aerosols into the NH during the climatologically important Laki volcanic eruption may have cooled the NH resulting in fewer North Atlantic TCs overall49; however, our results suggest that the eruption also shifted North Atlantic TC tracks to the south, resulting in relatively more Central American TC landfalls.…”
Section: Resultsmentioning
confidence: 53%
“…3). The large influx of sulphate aerosols into the NH during the climatologically important Laki volcanic eruption may have cooled the NH resulting in fewer North Atlantic TCs overall49; however, our results suggest that the eruption also shifted North Atlantic TC tracks to the south, resulting in relatively more Central American TC landfalls.…”
Section: Resultsmentioning
confidence: 53%
“…As for earlier eruptions, Guevara-Murua et al 8 analyzed reconstructions of TCs following major volcanic eruptions, and found a consistent reduction of North Atlantic TC activity in the 3 years following the eruptions. In addition to the fact that their finding is based on proxy reconstructions and not actual observations, they did not propose a mechanism to explain how high-latitude volcanic eruptions would cause a reduction of North Atlantic TC activity.…”
Section: Introductionmentioning
confidence: 82%
“…For instance, Stevenson et al 29 noticed that volcanic forcing can alter the Another possibility is that the volcanic eruptions modify the ITCZ location, which would also influence TC activity, as suggested in ref. 8 . Recently 30 showed in a modeling study that after Tamborastrength volcanic eruptions TC activity is modulated by the ITCZ response.…”
Section: Discussionmentioning
confidence: 99%
“…To comprehend the behavior of TC, it is important to identify the factors contributing to observed TC changes and quantify the response to external forcings, which lays a solid foundation for better future projection. Thus, intensive investigations have been performed to estimate the effect of anthropogenic and natural forcings on Atlantic hurricanes (Dunion & Velden, 2004;Dunstone et al, 2013;Emanuel, 2013;Gillett et al, 2008;Guevara-Murua et al, 2015;Holland & Webster, 2007;Knutson et al, 2008;Villarini & Vecchi, 2012). However, attentions are mainly paid on the short-term (i.e., centennial time scale) effect of increased greenhouse gases or short-lived forcings (e.g., volcanic aerosols).…”
Section: Introductionmentioning
confidence: 99%